Synthesis and Characterization of Gold Nanoparticles (AuNPs) by Utilizing Bioactive Compound of Imperata cylndrica L - Iwan Syahjoko Saputra; Siti Suhartati; Yoki Yulizar; Sudirman Sudirman (Jurnal Kimia Terapan Indonesia, 2020)
Gold nanoparticles (AuNPs) have been successfully synthesized using bioactive compounds of Imperata cylindrica L leaf extract. In this study, precursors used HAuCl4 7x10-4 M, 8x10-4 M and 9x10-4 M. Concentration of Imperata cylindrica L used was 5%. The colloid of Gold nanoparticle (AuNPs) formed were characterized using Ultraviolet-visible Spectrophotometer (UV-Vis), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD). The formation of gold nanoparticles (AuNPs) at concentration 9x10-4 M showed the best results with a color change to red. UV-Vis showed an absorbance value of 1.4 and a wavelength of 530 nm. FTIR analysis showed the interaction of -OH functional group on phenolic compounds of Imperata cylindrica L leaf extract with Au3+ ions. There was a shift on the peak at wavenumber 3414 cm-1 to 3404 cm-1, indicating the formation of Au nanoparticles. TEM analysis showed the morphology of AuNPs is sphere-shaped with a particle size of 20 nm. XRD analysis showed a crystal size average of gold nanoparticles is 12 nm.